Electrical, thermal, and viscoelastic properties of graphene nanoplatelet/poly(butylene adipate‐co‐terephthalate) biodegradable nanocomposites. Issue 27 (1st April 2016) - Kashi, Sima; Gupta, Rahul K.; Kao, Nhol; Bhattacharya, Sati N.
ABSTRACT: Graphene nanoplatelets (GNPs) were dispersed in poly(butylene adipate‐ co ‐terephthalate) (PBAT) by melt‐blending. Scanning electron micrographs showed good dispersion of GNPs in PBAT at low concentrations while at higher loadings, the platelets became physically in contact forming conductive pathways. Electrical conductivity of PBAT was enhanced markedly with GNP addition with a distinctly faster rate for GNP loadings higher than 6 wt % because of formation of conductive networks. Interestingly, thermal stability of PBAT was also found to increase for GNP loadings above 6 wt %. Dynamic viscoelastic properties of the nanocomposites exhibited significant enhancement with increasing GNPs. In particular, storage modulus showed less frequency dependency in the low frequency region leading to a percolation threshold of between 6 and 9 wt %, above which time–temperature superposition principle failed. Steady shear measurements revealed that GNP incorporation increased the zero‐shear viscosity markedly and intensified the shear thinning behavior. Carreau model well described the shear viscosity of all the compositions. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43620. Abstract :